2015
DOI: 10.1371/journal.pbio.1002048
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restriction-Mediated Replicative Lifespan Extension in Yeast Is Non-Cell Autonomous

Abstract: Calorie-restriction extends lifespan in many multicellular organisms; here substances secreted by calorie-restricted yeast are found to induce longer life in other yeast cells, suggesting that cellular communication is a component of this phenomenon even in a single-celled organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…S2–3). It is important to note that microfluidics-based lifespan measurements are free from potential non-cell autonomous effects while results obtained from the micromanipulator-based lifespan assay can be a combination of both cell autonomous and non-cell autonomous effects (Mei and Brenner, 2015), as during the application of the micromanipulator, cells can be exposed to small molecules that may be secreted to the solid growth surface during aging.…”
Section: Resultsmentioning
confidence: 99%
“…S2–3). It is important to note that microfluidics-based lifespan measurements are free from potential non-cell autonomous effects while results obtained from the micromanipulator-based lifespan assay can be a combination of both cell autonomous and non-cell autonomous effects (Mei and Brenner, 2015), as during the application of the micromanipulator, cells can be exposed to small molecules that may be secreted to the solid growth surface during aging.…”
Section: Resultsmentioning
confidence: 99%
“…The blueprints for multFYLM, as well as the image analysis pipeline are both available via GitHub (see Materials and methods). We note that microfluidics-based lifespan measurements are free from potential extrinsic effects (e.g., secretion of small molecules onto the solid agar surface) which have been proposed to confound observations of RLS assays using manual microdissection ( Mei and Brenner, 2015 ). Using the multFYLM, we set out to determine whether fission yeast undergoes replicative aging.…”
Section: Discussionmentioning
confidence: 99%
“…This is traditionally done via manual micro-dissection of sibling cells on agar plates, a laborious process that is especially difficult and error-prone for symmetrically dividing fission yeast. Extrinsic effects related to using a solid agar surface may confound observations made under these conditions ( Mei and Brenner, 2015 ). Finally, recent work using high-throughput microfluidic devices to study individual budding yeast and bacterial cells ( Lee et al, 2012 ; Crane et al, 2014 ; Wang et al, 2010 ; Liu et al, 2015 ; Jo et al, 2015 ; Nobs and Maerkl, 2014 ; Tian et al, 2013 ; Huberts et al, 2014 ; Minc and Chang, 2010 ) has shown that large sample sizes are needed to truly capture cellular lifespan accurately – populations less than ~100 cells do not reliably estimate the RLS ( Huberts et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also developed FYLM Critic, an image-processing pipeline for quantitative phenotypic analysis of individual cell lineages. We note that microfluidics-based lifespan measurements are free from potential extrinsic effects (e.g., secretion of small molecules onto the solid agar surface) which have been proposed to confound observations of RLS assays using manual microdissection (56). Using the multFYLM, we set out to determine whether fission yeast undergoes replicative aging.…”
Section: Discussionmentioning
confidence: 99%